Failure analysis of worn valve train components of a four-cylinder diesel engine. (October 2018) - Soffritti, C.; Merlin, M.; Vazquez, R.; Fortini, A.; Garagnani, G.L.
Abstract: This work investigates the causes of excessive wear occurring at the rocker arm/pushrod and rocker arm/valve interfaces of a diesel engine for industrial cleaning machines, after only 1000 h of engine operation. In this engine, the recent replacement of tappets by hydraulic valve lifters not only reduced the running time but also required supplementary maintenance. The chemical composition of the worn components was verified by optical emission spectroscopy. The microstructures, mechanical properties and surface textures were determined by optical microscopy, Vickers hardness and non-contact 3D profilometry. To evaluate the wear mechanisms, the worn surfaces were analyzed by scanning electron microscopy with energy dispersive spectroscopy. The results indicated non-uniform wear damage at the rocker arm/valve interface, probably due to a misalignment of valves with respect to valve seat inserts. For rocker arms and pushrods, improper austenitization parameters and/or unsuitable design of the inductor left some free ferrite, responsible for non-compliance with required specifications for the induction hardening treatment. All worn surfaces were characterized by material removal by scuffing; initiation of fatigue cracks was also observed at the rocker arm/valve interface, and probably erosive cutting occurred at the rocker arm/pushrod interface. Highlights: Excessive wear was detected in valve train components of a diesel engine. The cause was probably misalignment of valves with respect to valve seat inserts. The induction hardened regions of rocker arms and pushrods contained free ferrite. Scuffing and pits were detected at the rocker arm/valve interface. Scuffing and probably erosive cutting occurred at the rocker arm/pushrod interface.